Penyelesaian Perkara Pencurian dengan Pendekatan Keadilan Restoratif di Pengadilan - Bahari, Roni; Surbakti, Natangsa; Iksan, Muchamad (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research aims to understand how theft cases are resolved using the restorative justice approach in court. This study combines normative and empirical research methods. Subsequently, the collected data were analyzed qualitatively to describe the problem and address the research purposes. The results show that resolving theft cases with a restorative justice approach in court offers a new paradigm that not only focuses on applying retributive justice but prioritizes the processes of restoration and reconciliation between the Accused and the Victim. Through the implementation of Supreme Court Regulation Number 1 of 2024, the stages of case resolution with restorative justice from trial preparation to creating a restorative agreement ensure that the justice pursued is restorative. The effectiveness of this approach depends on the Victim’s willingness to forgive the Accused, the restoration of losses suffered by the Victim, and the Accused’s status as a non-recidivist. Therefore, it is recommended that Judges proactively facilitate dialogue between the Accused and the Victim and ensure that the restorative agreement adheres to the principles of proportionality and substantive justice. Public Prosecutors should more actively identify cases suitable for restorative resolution and prepare proof and physical evidence carefully to support the mediation process. The Accused and the Victim are encouraged to participate openly and honestly in mediation. In particular, The Victim needs encouragement to state their losses and needs clearly, and to consider the option of reconciliation as a step towards recovery. Finally, the community is expected better to understand the benefits and processes of restorative justice, thereby providing broader support for a criminal justice system oriented not only towards delivering retributive justice but also towards restoration and repairing social relationships in the future.